Acupuncture for post-stroke hiccup: an overview of systematic reviews - Liu, Xin-xin; Ma, Ying-qi; Su, You-zhu; Kong, Ling-yao; Shen, Chen; Liu, Jian-ping (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to describe and summarize the evidence from systematic reviews (SRs) of the efficacy and safety of acupuncture in the treatment of post-stroke hiccup and to provide a reference for clinical practice and future research.MethodsWe conducted a systematic search across eight electronic databases from their inception up to February 2025. This search encompassed systematic reviews focusing on acupuncture for post-stroke hiccup. The methodological quality was assessed using the AMSTAR 2. The corrected coverage area was used to calculate the degree of overlap of the original studies. The evidence quality was assessed using the GRADE approach.ResultsOf the 10 eligible systematic reviews included, the methodological quality was evaluated as 1 (10.00%) low and 9 (90.00%) very low quality. The corrected coverage area of the preliminary studies was moderate or high overlap. Acupuncture may alleviate hiccups symptoms and improve the quality of life (certainty: moderate to very low). Safety data were limited and insufficient to draw firm conclusions.ConclusionAcupuncture may be a potential intervention for the treatment of a post-stroke hiccup. These results should be interpreted with caution due to the methodological shortcomings and low evidence quality observed in current systematic reviews. There is an urgent need for more well-designed, high-quality randomized controlled trials.